Penumbuhan Motivasi Belajar Serta Pengenalan Dampak Gadget pada Anak Sekolah Dasar - Agus Kurnia; Shendy Arya Kusuma; Abi Rizka Yulia Arimanda; Natasya Dyahayu Lestari (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
The use of gadgets in elementary school children in Indonesia, including in West Nusa Tenggara Province (NTB), is increasingly widespread and has had a significant impact on their motivation to learn and behavior. This service activity aims to develop a community service program that focuses on increasing learning motivation and awareness of the negative impact of gadget use on elementary school children in NTB. The community service method is carried out through the Participatory Action Research approach which is designed to increase awareness of the importance of intrinsic learning motivation and strengthen understanding of the negative impact of excessive use of gadgets. Pre-test and post-test are carried out by giving questionnaires to students, then analyzed descriptively. The results showed a significant increase in students' learning motivation and their understanding of the adverse effects of gadgets. Teachers also reported positive changes in the level of student engagement in the classroom learning process. This service activity highlights the importance of the role of community service in overcoming the challenges of modern education, especially related to the use of technology in children. The implications of this program are expected to have a positive impact on improving the quality of education and the welfare of elementary school children in NTB.